Assessing investment priorities for driving inclusive agricultural transformation in Tanzania - Aragie, Emerta A.; Benfica, Rui; Pauw, Karl; Randriamamonjy, Josee; Thurlow, James (International Food Policy Research Institute, 2023)
This study utilizes a recursive dynamic general equilibrium model calibrated with data for Tanzania to explore the link between agricultural and rural development spending and four development outcomes: economic growth, job creation, poverty reduction, and diet quality. Results show that no single expenditure option is the most effective in achieving all four desired development outcomes for Tanzania. Productivity-enhancing agricultural interventions in horticulture are effective at generating growth in the agri-food system (AFS) and improving diets, but have a limited effect on employment. Supporting cereal producers has large effects on growth and poverty reduction, with relatively high returns per dollar invested, but its effect on diet quality is weak. Providing livestock services to milk and poultry farmers consistently ranks high across the outcome indicators, with strong employment effects on downstream AFS. Crop research and development and feeder roads generate moderate impacts on all four outcomes. Partially reallocating the budget towards the most cost-effective spending options can substantially increase the development effectiveness for Tanzania of agriculture sector support expenditures. The approach adopted in this study can help policymakers design and prioritize agricultural interventions and expenditure portfolios that better reflect the country’s broad food system.